Grand Strategies of Weak States and Great Powers - Kassab, Hanna Samir (Springer International Publishing, 2018)
Grand strategies can be thought of as overall survival strategies of states of all states. Great powers seek survival against other great powers seeking to undermine their power, position determining prestige-seeking behavior as psychotic and destructive. Weak states suffer from systemic vulnerabilities and trade whatever political power they have to a great power for economic assistance. If enough weak states support a particular great power, then that great power will become more powerful relative to competitors. This forms an international system fashioned by these transactions. Hanna Samir Kassab is Assistant Professor at Northern Michigan University, USA.